Studies on bactericidal efficacy of pumpkin (Cucurbita moschata Duchesne) peel - Ahmed, Qamar Uddin (Coastal Life Medicine Media co., Limited, 2014)
Objective: To explore the in vitro antibacterial potential of the peel of Cucurbita moschata Duchesne (tropical pumpkin) (C. moschata) against human pathogenic bacteria. Methods: In the present study, dichloromethane (DCM), methanol (MEOH) and aqueous (AQ) extracts of C. moschata peel were examined for in vitro antibacterial potency against eight bacterial strains i.e. Bacillus cereus, Burkholderia cepacia, Escherichia coli, Enterococcus faecalis, Staphyloccocus aureus, Pseudomonas aerugenosa, Vibrio alginolyticus, Vibrio parahaemolyticus using Kirby-Bauer disk diffusion susceptibility and broth micro-dilution methods. Results: DCM extract of pumpkin peel exhibited the maximum zone of inhibition against S. aureus (21 mm) whereas aqueous extract of pumpkin peel revealed the least zone of inhibition against E. coli (8 mm). Methanol extract gave maximum zone of inhibition against P. aerugenosa (19 mm). Broth micro-dilution method showed minimum inhibitory concentration (MIC) for the DCM extract against B. cepacia at 6.25 mg/mL. The minimum bactericidal concentrations (MBC) were also determined to know the nature of all extracts. DCM and MEOH extracts exhibited bactericidal nature to all bacterial strains except for the V. alginolyticus. The MBC values exhibited bactericidal nature ranged from 3.12 mg/mL to 100.00 mg/mL. The screening of antimicrobial properties of different extracts of C. moschata peel revealed that the DCM extract possesses good antimicrobial efficacy compared to MEOH and AQ extracts. Conclusions: Peel of C. moschata possesses antibacterial compounds and could be potential source for a new class of antibiotics.